Checklist and key for identification of larvae of Hydropsyche species (Hydropsychidae, Trichoptera) of the Maghreb - Bemmoussat-Dekkak, Soumya; Abdellaoui-Hassaine, Karima; Zamora-Muñoz, Carmen (Zootaxa, 2021)
Twelve species of the genus Hydropsyche (Trichoptera) are reported from the Maghreb; six in Tunisia, eight in Morocco, and eleven in Algeria. These three North African countries are inhabited by common species, except that H. siltalai has been reported only from Algeria and H. pandiel only from Morocco. A list of Hydropsyche species known from the Maghreb is presented and a key for identification of described larvae of Maghreb Hydropsyche species is provided.